Some Results on Related Fixed Point Theorems in Two $S$-Metric Spaces - Hakan Karayılan (Journal of New Theory)
In this study, by considering the technique in the theorem of Bollenbacher and Hicks, we obtain some related fixed point theorems involving two mappings on two related complete $S$-metric spaces with certain conditions. As the applications of the main theorem, we then derive some new related fixed point theorems involving a pair of mappings in such spaces. We finally discuss the need for further research.